Chronic kidney disease in children - Becherucci, Francesca; Roperto, Rosa Maria; Materassi, Marco; Romagnani, Paola (Clinical kidney journal, 2016)
Chronic kidney disease (CKD) is a major health problem worldwide. Although relatively uncommon in children, it can be a devastating illness with many long-term consequences. CKD presents unique features in childhood and may be considered, at least in part, as a stand-alone nosologic entity. Moreover, some typical features of paediatric CKD, such as the disease aetiology or cardiovascular complications, will not only influence the child's health, but also have long-term impact on the life of the adult that they will become. In this review we will focus on the unique issues of paediatric CKD, in terms of aetiology, clinical features and treatment. In addition, we will discuss factors related to CKD that start during childhood and require appropriate treatments in order to optimize health outcomes and transition to nephrologist management in adult life.